2015
DOI: 10.3390/ijms16059976
|View full text |Cite
|
Sign up to set email alerts
|

Sasa quelpaertensis Leaf Extract Inhibits Colon Cancer by Regulating Cancer Cell Stemness in Vitro and in Vivo

Abstract: A rare subpopulation of cancer cells, termed cancer stem cells (CSCs), may be responsible for tumor relapse and resistance to conventional chemotherapy. The development of a non-toxic, natural treatment for the elimination of CSCs is considered a strategy for cancer treatment with minimal side effects. In the present study, the potential for Sasa quelpaertensis leaf extract (SQE) and its two bioactive compounds, tricin and p-coumaric acid, to exert anti-CSC effects by suppressing cancer stemness characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 57 publications
2
38
0
Order By: Relevance
“…SQE has shown beneficial effects on colitis in previous studies. Moreover, the bioactive component of SQE, tricin and p -coumaric acid, have exhibited antioxidant, anti-inflammatory, and anticancer effects which remain to be investigated in relation to gut microbiota [17, 18, 20, 34]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…SQE has shown beneficial effects on colitis in previous studies. Moreover, the bioactive component of SQE, tricin and p -coumaric acid, have exhibited antioxidant, anti-inflammatory, and anticancer effects which remain to be investigated in relation to gut microbiota [17, 18, 20, 34]. …”
Section: Discussionmentioning
confidence: 99%
“…Its leaf extract has been reported to mediate various health promoting properties, including anti-inflammation, anti-cancer effects, and anti-obesity effect [1618]. Sasa quelpaertensis leaves extract (SQE) is a mixture of polysaccharides, amino acids, and polyphenols, including p -coumaric acid and tricin, and has exhibited anti-inflammatory and anti-obesity effects [19, 20].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro studies have indicated that p ‐CA moderately inhibits the growth of some tumour cell lines. p ‐CA significantly decreases the viability of neuroblastoma N2a cells (EC 50 = 104 µmol L −1 ), human lung A549, colon HT29‐D4, and cancer stem cells . However, it inhibits Caco‐2 and ECV304 cells only at high concentrations of up to 1.5 mmol L −1 and 5 mmol L −1 , respectively .…”
Section: Biological Activitiesmentioning
confidence: 99%
“…Withaferin-A (WA), a bioactive compound derived from Withania somnifera, inhibits Notch-1 signaling and cell proliferation in three colon cancer cell lines [286]. Two bioactive compounds (tricin and p-coumaric acid) present in leaf extract of Sasa quelpaertensis Nakai (Poaceae) are able to inhibit the growth of CSCs deriving from different colon cancer cell lines through Dll-1 and Notch-1 inhibition and downregulation of biomarkers related to tumor vascularization (VEGF and HIF-1α) [287]. Curcumin inhibits the activation of Notch-1 and the expression of Jagged-1 as well as HES1 in esophageal cancer cell lines [288].…”
Section: Nutraceuticals Acting Through the Notch Pathwaymentioning
confidence: 99%